Transnasionalisme dan Translasi Budaya Melalui Media Televisi “Studi pada Trend Hallyu di Indonesia” - Retno Mustikawati (Rekam: Jurnal Fotografi, Televisi, Animasi)
Cultural images, fantasies and imaginations are formed differently depending on location technology and characteristic of cultural consumption. When cultures of of different “symbolic structures” across national bounderies, they are influenced by historically accumulate images that each nation holds of one another. Culture consists of knowledges, beliefs, perceptions, attitudes, expectations, values and patterns of behavior that people learn by growing up in a given society. A media such as television occupies an important place in culture and society. Media messages are perceived differently according to the diverse backgrounds, cultures and life-styles of audiences. Culture as a strategy of survival is both transnational and translational. It is transnational because ithas to have physical centers somewhere, places in which, or from where, their particular meanings are produced. Culture is translational because such spatial histories of displacement now accompanied by the territorial ambitions of global media technologies.Television plays a very important role in a society. It can change opinions because it has access to audiences and gives a lot of strength. The strength that can either be used constructively or destructively. Their programs have an impact and people as the audiences listen to them.